A Cross-Sectoral Coordination in One Health: A Case Study of Anthrax Prevention and Control in Maros, Indonesia - Nur Azizah Azzahra; Dwi Sutiningsih; Mateus Sakundarno Adi; Nurul Fuadi Yusuf; Khairunnisaa; Rifka Haristantia; Nur Mila Sari; Amilah Eka Putri; Trisna Widyanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: This study aimed to explore how the One Health (OH) approach was applied in the prevention and control of anthrax in Maros Regency, an anthrax-endemic area of Indonesia with recurrent human and animal cases. With the continued public health threat posed by anthrax as a zoonotic disease, especially in endemic regions, our objective was to assess intersectoral coordination and collaboration efforts to address gaps in disease prevention identified in existing literature. Methods: This qualitative study involved a case study design conducted across the Maros Regency from February 2022 to June 2022. A total of 29 informants were enrolled, including 17 from the human health sector, five from the animal health sector, and seven from local government, through purposive sampling method. Ethical approval was obtained from the Health Research Ethics Committee of Public Health Faculty, Diponegoro University (Approval Number: 74/EA/KEPK-FKM/2022), and all participants provided informed consent. Results: The primary outcome of the study was the One Health approach has been applied in the Maros Regency, including sharing information; cross-sectoral meetings; coordination and collaboration. Conclusion: In conclusion, our study contributes to the understanding of anthrax prevention and control by highlighting the role and implementation of the One Health approach in an anthrax-endemic setting. This research provides insights into the practical benefits of cross-sectoral coordination and shared responsibilities. Future studies should explore strategies to institutionalize One Health mechanisms and evaluate their impact.